Conspecific negative density dependence does not explain coexistence in a tropical Afromontane forest. (17th February 2021) - Abiem, Iveren; Dickie, Ian; Kenfack, David; Chapman, Hazel
Abstract: Questions: A leading hypothesis for species coexistence in species‐rich, lowland tropical forests is conspecific negative density dependence (CNDD), driven by host‐specific pests and pathogens and competition for available resources. The extent to which this applies to Afromontane forests with relatively low diversity, a high frequency of single‐species stands, relatively few pests and pathogens and larger edge:core ratios, is unknown. We hoped that the results of our investigation would either confirm the generality of CNDD across these different tropical forest types or offer novel insights into alternative mechanisms leading to the maintenance of Afromontane tree species diversity. Location: Ngel Nyaki Forest Reserve, southeastern Nigeria. Methods: We monitored the survival of 10, 741 seedlings of 93 species over two years in a long‐term Forest Global Earth Observatory (ForestGEO) study plot in a montane forest in Nigeria. We assessed the effect of conspecific and heterospecific seedling and adult neighbours on the survival of every seedling and seedling guild (shade vs light‐demanding; canopy vs understorey; edge specialists vs generalists; small vs large seedlings). Results: We found strong evidence for non‐species‐specific positive and negative density dependence. CNDD was stronger in canopy species and light‐demanding species than in the other growth form and shade tolerance guilds. Conclusions: Our study offers some clear predictions about drivers of community coexistence in this environment, which will require further testing using field‐based experiments. Abstract : We investigated the effects of plant neighbourhood densities on seedling survival in a tropical Afromontane forest. We found non‐species‐specific positive and negative density dependence. Seedling neighbours reduced seedling survival while adult neighbours increased seedling survival at the community level. However, the effect of neighbours on seedling survival varied across species growth forms, shade tolerance levels and seedling size groups.